DEVELOPING AN INTEGRATED MODEL ON FOOD WASTE CONSUMER BEHAVIOUR IN ROMANIA - Daniel NIJLOVEANU; Victor TIȚA; Nicolae BOLD; Toma Adrian DINU; Adrian George PETICILĂ; Cosmina Andreea SMEDESCU; Costel MIHALAȘCU; Marian STOIAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food waste is one of the most unusual behaviours related to economic systems located on the agrifood chain. In this matter, the study of the food waste and the mechanisms that lead to its development are complex and rooted within several components of the human behaviour and economic system dynamic. In this paper, we propose the development of a model which presents the dynamics of the phenomenon based on several cause-effect relationships between aspects of human behaviour and economic aspects. The model is built using a Systems Dynamic (SD) approach, based on the identification of connections between identified causes and effects and the determination of the ontologic and mathematical nature of the connections.